Swing, sing & think David Fray records Johann-Sebastian Bach - Bach, Johann Sebastian 1685-1750; Bach, Johann Sebastian 1685-1750; Bach, Johann Sebastian 1685-1750 (Idéale Audience - Arte, 2008)
Bruno Monsaingeon's camera immerses us in the private world of David Fray "recreating" three concertos for keyboard and orchestra by Johann Sebastian Bach. Although Major musical figures such as Gould, Richter, Menuhin or Varaday are part of Bruno Monsaingeon's universe, the filmmaker also likes to share his discoveries of young artists. As in the cases of Piotr Anderszewski and the violinist Valery Sokolov several years ago and today with the pianist David Fray who was born in 1981. The critics had already noticed David Fray with his first CD which cleverly associated Bach and Boulez and that Virgin Classics distributed under its label in 2007. But in June 2006, a concert at the Théâtre du Châtelet 2006 put him in the limelight: he replaced Hélène Grimaud at the last minute and in the same programme. A triumph. But David Fray isn't afraid of being in the limelight. He lets Bruno Monsaingeon film the recording of his first record for Virgin Classics in January 2008 with "Deutsche Kammerphilarmonie Bremen" which he directs from the piano with a programme that includes four of the most famous concertos for keyboard and orchestra by Bach. But how can one play Bach after Gould? This is what Bruno Monsaingeon proposes to show us. We see David Fray at home, in Paris, working on the score and explaining the different options open to him. Then in Bremen, during rehearsals with the orchestra, as he conveys to the musicians his vision of the works with astonishing passion and spontaneity. As the title of the film "Swing, Sing and Think" suggests, it is this same inspiration that Fray breathes into the three Bach Concertos in A Major BWV 1055, in F Minor BWV 1056 and in G Minor BWV 1058. By immersing us in the private world of the pianist, by retracing the musical gesture that leads to the interpretation of the work, or rather to its "re-creation," the film also immerses us in these masterpieces by Bach? That is not the least of the film's merits